Horticultural Therapy - Sydney Park Brown; Eva C. Worden; Theodora M. Frohne; Jessica Sullivan (EDIS)
Horticultural therapy is the practice of engaging people in plant or gardening activities to improve their bodies, minds, and spirits. Research confirms that healthful benefits accrue when people connect with plants by viewing, planting, growing, and/or caring for them. This revised 3-page fact sheet describes the history and benefits of horticultural therapy and includes references and links to additional resources. It was written by Sydney Park Brown, Eva C. Worden, Theodora M. Frohne, and Jessica Sullivan, and published by the UF Department of Environmental Horticulture, January 2011.